KARAKTERISTIK SIFAT MEKANIK KOMPOSIT SERAT BAMBU RESIN POLYESTER TAK JENUH DENGAN FILLER PARTIKEL SEKAM - Budiman, Agus; Sugiman, Sugiman (Dinamika Teknik Mesin, 2016)
This paper presents the effect of volume fraction of rice husks on the mechanical properties of bamboo fiber/unsaturated polyester composites. The composite specimens were made from bamboo fiber with fixed volume fraction of 40% and rice husk particle as filler with volume fractions varied 0%, 10%, 20% and 30%. Matrix used was unsaturated polyester resin. Bamboo fibers and rice husk were surface treated using alkali solution 4% (by weight) for 2 hours. The manufacturing process of composite was using hand layup method. The specimens were tested in tension, bending and in impact loading. The results show that the addition of rice husk particles up to volume fraction of 20% does not result in a decrease of tensile strength, but after a volume fraction of 20%, the tensile strength tends to decrease. In bending test, the rice husk volume fraction up to 20% increase the bending strength, but after that then it tends to decrease. However the bending modulus seems unaffected by the volume fraction of rice husk. Similar to the bending modulus, the impact strength is not significantly affected by the volume fraction of rice husk.